An overview of pharmacological approaches for management and repair of spinal cord injuries. - Alireza Khoshnevisan; Azam Mardani; Shahab Kamali (Iranian Journal of Psychiatry, 2010)
Spinal cord injury (SCI) leads to loss of nervous tissue and consequently to catastrophic neurological deficits. Up to now there is no definite treatment available that restores the loss of function to a degree that an independent life can be guaranteed.This justifies the cost of research into the new modalities for a treatment of SCIs. In current paper, recent developments and new approaches in pharmacological therapy have been reviewed.